(untitled) (Fiep Bulletin - online, 2015)
Many are the investigations that can appear by means of the terms discrimination and exclusion, already that we live in a society where hidden situations of intolerance occur had as some cultures gifts no Brazil. To obtain to identify these situations, this study it searched the actions of the professors of Physical Education of Basic Education and Average Education in relation to the discrimination and exclusion carried through for its pupils. We use an established qualitative analysis in comments and notations of the actions of the professors. The results had shown that the same teacher who combat to the discrimination and the exclusion also can be the responsible one for he sprouting of these situations, moreover, pupils and/or the teachers discriminate or exclude due: the ability, the sort question, for being above of the weight or being obese and due to aesthetic. We conclude that the society unhappily where we live, rich for its miscegenation it is poor wit relation to the tolerance the differences and that the professors of the schools have problematic a so ample one in the hand that must better be studied and consequently prevented.